financial performance analysis of companies using a management accounting approach in the creative industry sector: Array - jelita puspita mardani puspita (STIESA Press, 2025)
This study aims to analyze the impact of management accounting implementation on the financial performance of companies in the creative industry sector. Although the creative industry contributes significantly to Indonesia’s Gross Domestic Product, businesses in this sector continue to face financial management challenges, particularly due to revenue uncertainty and high production costs. Management accounting plays a crucial role in providing relevant information for strategic decision-making, cost control, and budget planning. This research employs a quantitative approach using a survey method involving 30 purposively selected creative industry companies. Data were collected through questionnaires and analyzed using simple linear regression. The results show that the application of management accounting has a positive effect on financial performance, especially in improving cost efficiency, profitability, and strategic decision-making. These findings highlight the importance of enhancing management accounting literacy among creative industry players to strengthen their competitiveness and business sustainability.